Becoming a powerhouse librarian : how to get things done right the first time - Gray, Jamie M. (Medical Library Association books., 2017)
"Becoming a Powerhouse Librarian will help you recognise and implement specific behaviours and actions librarians can use to successfully drive projects forward, institute new services or revamp old ones, and establish key relationships both inside and outside of the library. Each behaviour or trait covered can be either developed or strengthened within an individual or team. The book features practical tips to build skills in each topic area. Examples of topics found in this book include: lifelong learning, risk-taking, creativity, identifying and leveraging stakeholders, creating balance, knowing when to lead and when to follow, handling setbacks and avoiding burnout. Whether you're just beginning your library career or you're a seasoned professional, Becoming a Powerhouse Librarian is sure to have something for you." -- Provided by publisher.